Four-Year Experience of Digital Slide Telepathology for Intraoperative Frozen Section Consultations in a Two-Site French Academic Department of Pathology. Issue 3 (27th May 2020) - Laurent-Bellue, Astrid; Poullier, Eric; Pomerol, Jean-François; Adnet, Eric; Redon, Marie-José; Posseme, Katia; Trassard, Olivier; Cherqui, Daniel; Zarca, Kevin; Guettier, Catherine
Abstract: Objectives: To share our experience with digital slide telepathology for intraoperative frozen section consultations (IOCs) and to describe its evolution over time by reporting performance metrics and addressing organizational and economic aspects. Methods: Since 2013, a technician has been alone at the surgical site. At the other site, the pathologist opens the digital slide from a local server via the intranet. Three periods were compared: a 6-month period of conventional IOC (period 1), a 24-month period of telepathology at 6 months after implementation (period 2), and a 12-month period of telepathology at 3.5 years after implementation (period 3). Results: In total, 87 conventional IOCs and 464 and 313 IOCs on digital slides were performed respectively during periods 1, 2, and 3; mean turnaround time was 27, 36, and 38 minutes, respectively, and there were a mean number of 1.1, 1.1, and 1.3 slides, respectively, per IOC. Diagnostic accuracy was achieved in 95.4%, 92.7%, and 93.9%, respectively, of IOCs (not significant). The additional cost is in the same range as the cost of urgent transport by courier. Conclusions: Developing IOC with digital slides is a challenge but is necessary to optimize medical time in the current context of pathologist shortage and budget restrictions.